Damage Map of Facades of Historic Buildings: Case Study of the Madre de Deus Church in Recife-PE - Nascimento, Thulio Roberto Silva do; Rodrigues , Stephany Rayane Silva; Barreto, Lydia Marques; Monteiro, Eliana Cristina Barreto; Soares, Willames de Albuquerque (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Facades, in addition to their aesthetic function, play a fundamental role in the preservation of a building, acting as a protective barrier against external aggressive agents. Therefore, maintenance activities are essential to prolong the lifespan of this system and prevent the degradation of its components. When it comes to historical heritage, beyond the sustainability brought by maintenance activities, conserving the architectural richness of a specific era is vital for the history and culture of a place. The damage map is a crucial document for developing a restoration project for historical and religious buildings. The present research was developed with the purpose of stimulating the appreciation of heritage riches and collaborating with the development of actions aimed at the preservation and conservation of the National Cultural Heritage, through the creation of a damage map and analysis of the pathological manifestations of the facades of the Madre de Deus Church, Recife/PE. The Madre de Deus Church was selected based on criteria such as: classification by the National Historic and Artistic Heritage Institute; social importance; accessibility; and data availability. Research on the building’s history and visual inspections were carried out. The main manifestations identified were dirt/biofilm and stains due to the presence of moisture. The South Facade is the most critical of the building, requiring more significant interventions for restoration, which may be related to the higher incidence of winds and rains.